Isolation and Characterization of Lytic Bacteriophage Against Multi-drug Resistant Pseudomonas aeruginosa - Maharjan, Archana; Nepal, Roshan; Dhungana, Gunaraj; Parajuli, Apshara; Regmi, Madhav; Upadhyaya, Elisha; Mandal, Dipendra; Shrestha, Mitesh; Pradhan, Pragati; Manandhar, Krishna Das; Malla, Rajani (Journal of Nepal Health Research Council, 2022)
Background: Pseudomonas aeruginosa is a Gram-negative opportunistic pathogen frequently causing healthcare-associated infections. The apocalyptic rise of antimicrobial resistance has rekindled interest in age-old phage therapy that uses phages (viruses that infect bacteria) to kill the targeted pathogenic bacteria. Because of its specificity, phages are often considered as potential personalized therapeutic candidate for treating bacterial infections. Methods: In this study, we isolated and purified lytic phages against multi-drug resistant P. aeruginosa using soft agar overlay technique. Phage characteristics like thermal and pH stability, latent period and burst size were determined using one-step growth assay while multiple host range spectrum was determined by spot assay. The phages were further characterized using protein profiling. Results: Three Pseudomonas phages (øCDBT-PA31, øCDBT-PA56 and øCDBT-PA58) were isolated from the holy rivers of Kathmandu valley. Among 3 phages, øCDBT-PA31 demonstrated multiple host range and could lyse multi-drug resistant strain of P. aeruginosa. Further, øCDBT-PA31 showed latent period of 30 minutes with corresponding burst sizes of 423-525 PFU/cell. Interestingly, øCDBT-PA31 also tolerated a wide range of adverse conditions, such as high temperature (50°C) and pH 3-11. Further, protein profiling revealed that øCDBT-PA31 has 4 and øCDBT-PA11 had 3 distinct bands in the gradient gel ranging from approximately 3.5-29 kilodaltons (kDa) suggesting them to be morphologically distinct from each other. Conclusions: As multi-drug resistant bacteria are emerging as a global problem, lytic phages can be an alternative treatment strategy when all available antibiotics fail. Keywords: Antimicrobial resistance (AMR); bacteriophage; P. aeruginosa; phage therapy; SDS-PAGE.